Evolution of Carbon Fiber Microstructure During Carbonization and High-Temperature Graphitization Measured In Situ Using Synchrotron Wide-Angle X-ray Diffraction. Issue 1754 (22nd June 2015) - Behr, Michael; Rix, James; Landes, Brian; Barton, Bryan; Hukkanen, Eric; Patton, Jasson; Weigand, Steven; Keane, Denis
ABSTRACT: This paper will discuss the structure-property model developed that correlates the tensile modulus to the elastic properties and angular distribution of constituent graphitic layers for carbon fiber derived from a polyethylene precursor. In addition, a high-temperature fiber tensile device was built to enable heating of carbon fiber bundles at a variable rate from 25 °C to greater than ∼2300 °C, while simultaneously applying a tensile stress. This capability combined with synchrotron wide-angle x-ray diffraction (WAXD), enabled observation in situ and in real time of the microstructural transformation from different carbon fiber precursors to high-modulus carbon fiber. Experiments conducted using PAN- and PE-derived fiber precursors reveal stark differences in their carbonization and high-temperature graphitization behavior.